Monosaccharide compositions of sulfated chitosans obtained by analysis of nitrous acid degraded and pyrazolone-labeled products. (20th January 2016) - Han, Zhangrun; Zeng, Yangyang; Zhang, Meng; Zhang, Yiran; Zhang, Lijuan
Highlights: A novel method for determination of monosaccharides in sulfated chitosan was developed. The structure and sulfated degree of chitosan were also revealed. The reliability of the method was confirmed by online LC–MS analysis. The accuracy of our measurement was improved compared to established methods. This method could be used by any laboratory equipped with a HPLC and an online UV detector. Abstract: Chemically sulfated chitosans are important biomaterials. However, a reliable analytical method for quality control over such compounds is still lacking. In this study, we prepared four different kinds of selectively sulfated chitosans and developed a novel method to analyze their monosaccharide compositions by HPLC. In this method, nitrous acid was used to generate 2, 5-hydro mannose (M), 3-O-sulfated M (M3), 6-O-sulfated M (M6), and 3, 6-O-disulfated M (M9) from the sulfated chitosans. PMP, that is 1-phenyl-3-methyl-5-pyrazolone with a UV absorbance at 245 nm, was used to label all the Ms quantitatively. The monosaccharide compositions for each sulfated chitosan were obtained by C18 HPLC separation and online UV detection of all PMP-labeled Ms. The identities of all Ms were confirmed by MS analysis with the help of standard Ms generated from a heparin pentasaccharide and chitosan. The overall results indicated that the newly developed method had advantages over 13 C NMR in defining the monosaccharide compositions of sulfated chitosans and was useful for quality control purpose.